Numerical Simulation and Analytical Validation of the Drive and Transmission Mechanism for Truck Vehicles - Peter Droppa; Matúš Riečičiar; Karol Semrád; Katarína Draganová (Applied Sciences)
Nowadays, many various types of drive and transmission mechanisms characterized by various parameters and characteristics for different types of vehicles have been designed, developed and optimized with regard to the featured applications. Our research is focused on the creation of a complex simulation model of the drive and transmission mechanism of the vehicle Iveco LMV 4 × 4 M65. The correctness of the simulation model was verified using an analytical approach. The created numerical simulation model will serve as a basis for the further optimization of dynamic, operational and economical parameters of the vehicle. As the modification or replacement of the particular components of the drive and transmission mechanism is very complicated regarding the vehicles used in military operations, our research is focused on the enhancement of the control processes. More specifically, the main goal of the presented research activities is the modification of the gearshift logic and the adjustment of the gearshift map in order to improve the dynamic properties of the vehicle and, at the same time, reduce the fuel consumption. In spite of its complexity, the proposed simulation model can serve as a basis for the optimization of not only the gearshift control under specific input or output quantities and operational or environmental conditions but also for the simulation of the system behavior with modified or replaced components of the drive and transmission mechanism of this type of truck vehicle.